Industrialization and Social Mobility in Rural Communities: Navigating Economic Transitions and Community Development - Ampong, Djata; Maharati2 , Arai Maharati; Ardiyanti, Arini (Jurnal Sosial, Sains, Terapan dan Riset (Sosateris), 2024)
This research delves into the intricate relationship between industrialization and social mobility within rural communities, aiming to comprehend the multifaceted dynamics shaping economic transitions and mobility pathways. Employing a mixed-methods approach, this study amalgamates quantitative analyses and qualitative insights to explore correlations, trends, and significant observations in industrializing rural areas. The empirical findings reveal correlations between the level and nature of industrialization and indicators of social mobility. While diversified industrial landscapes offer pathways for economic advancement, disparities persist, influenced by educational access, industry type, and historical socio-economic imbalances. Integrating these findings with established literature and theories, including Structural Transformation, Human Capital, and Community Resilience frameworks, illuminates the complexities inherent in the interplay between economic shifts and societal dynamics. The study's implications advocate for inclusive policies prioritizing education, equitable economic development, and community resilience. Addressing limitations and biases inherent in the research unveils avenues for further investigation, emphasizing longitudinal studies, sector-specific analyses, and explorations into cultural preservation amidst economic transitions.